Impaired AIS plasticity in ankyrin-G mutant mice alters cortical excitability and behavior - Min Li; Bingqing Zhao; Zhimin Lu; Liu Zhe; Yue Han; Yating Chen; Huichao Wang; Yu Wang; Chunsheng Wu; Mingjie Zhang; Keyu Chen; Rui Yang (Proceedings of the National Academy of Sciences, 2025)
The developing brain undergoes neuroplasticity driven by learning, experience, and memory formation. The axon initial segment (AIS) is a specialized membrane domain within the proximal axon that initiates action potential. Studies have demonstrated that the AIS exhibits plasticity by altering its length and/or localization to adjust the excitability in response to neural stimuli. However, how AIS plasticity may affect brain function is unclear. The 480-kDa giant ankyrin-G protein (gAnkG) is the master organizer of AISs and nodes of Ranvier. Previously, we reported that a neurodevelopmental disorder-linked variant (Thr1861Met) in the neuron-specific domain of gAnkG causes the formation of diffused AISs in cultured ankyrin-G null neurons. Here, we generated a knock-in mouse harboring this mutation. The knock-in mice displayed impairments in motor coordination and social interaction. Neurons from these knock-in mice formed elongated AISs with no significant reduction in the accumulation of key AIS components-including ankyrin-G, β4-spectrin, voltage-gated sodium channels, and neurofascin. Crucially, unlike wild-type AISs, which shorten in response to stimulation by high K + or chemogenetics (designer receptors exclusively activated by designer drugs), the elongated AISs in mutant neurons failed to undergo such shortening, indicating a deficit in AIS plasticity. Neurons in the primary motor cortex and anterior cingulate cortex of knock-in mice exhibited AISs of normal length at early stage but failed to undergo the developmental shortening observed in wild-type neurons; by postnatal day 60, this resulted in elongated AISs and increased neuronal excitability in these regions. Thus, the gAnkG protein mutation impairs activity-dependent AIS plasticity, leading to abnormal neuronal excitability and behavioral deficits.